Non-iterative phase hologram generation with optimized phase modulation - Chen, Lizhi; Zhang, Hao; Cao, Liangcai; Jin, Guofan (Optics express, 2020)
A non-iterative algorithm is proposed to generate phase holograms with optimized phase modulation. A quadratic initial phase with continuous distributed spectrum is utilized to iteratively optimize the phase modulation in the reconstruction plane, which can be used as an optimized phase distribution for arbitrary target images. The phase hologram can be calculated directly according to the modulated wave field distribution in the reconstruction plane. Fast generation of the phase holograms can be achieved by this non-iterative implementation, and the avoidance of the random phase modulation helps to suppress the speckle noise. Numerical and optical experiments have demonstrated that the proposed method can efficiently generate phase holograms with quality reconstructions.